Eco Enzymes Application in Nitrite and pH Reduction Study in The River Water Samples - Wikaningrum, Temmy; Laily Thoatil Hanan (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
One of the pollutants that must be controlled in rivers is the level of nitrite. Excessive amounts of nitrite are detrimental because they affect the quality and health of aquatic ecosystems. This study aimed to determine the effectiveness of eco enzymes in reducing nitrite levels in polluted river water as an alternative to conventional water treatment technologies. Three types of eco-enzyme made from vegetable, tomato and orange waste were used in this study. The experiment also aimed to evaluate the potential of reducing nitrite levels and its effect on pH performance. The results showed that adding 5% Vegetables Eco Enzyme (VEE), Tomatoes Eco Enzyme (TEE) or Oranges Eco Enzyme (OEE) to river water samples with an initial nitrite level of 4.813 mg/L produced the best results, with VEE showing the greatest effectiveness. This is because the nitrite concentration was reduced by 100% in the 4^(th) hour for VEE, the 6^(th) hour for TEE and the 8^(th) hour for OEE. For the pH parameter, there was a significant decrease, but it remained within the quality standard of pH 6–9. Statistical analysis using t-tests and ANOVA showed significant differences in both nitrite levels and pH results, as well as in the type of treatment.